Implementasi Kultur Sekolah dan Praktik Pembelajaran Vokasional: Studi Etnografi di SMK Negeri 5 Sidrap - Suardi Zain; Muhammad Dirga Mubaroq; Muh Fadhil; Yaltaji Ilallah; Zakiah Nur Batoa (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Vocational education plays a strategic role in preparing human resources who are both technically competent and strong in character. This study aims to analyze the implementation of school culture and vocational learning practices at SMK Negeri 5 Sidrap, as well as to identify supporting and inhibiting factors affecting learning effectiveness. Employing an educational ethnography approach, data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the Miles & Huberman model through data condensation, display, and verification stages. The results indicate that a school culture rooted in religious values and discipline successfully shapes students’ character, although its implementation remains uneven across classes. Learning practices integrate student-centered approaches with digital technology use but face constraints such as limited practice equipment ratios and student ability heterogeneity resulting from the zoning policy. Teachers’ adaptive efforts through differentiated instruction, peer tutoring, and personal mentoring help reduce learning disparities. This study highlights the importance of synergy among school culture, pedagogical innovation, and transformative leadership to realize vocational education that produces not only technically skilled graduates but also individuals with strong character and readiness for the global workforce.